How to Study Chronic Diseases—Implications of the Convention on the Rights of Persons with Disabilities for Research Designs - von Peter, Sebastian; Bieler, Patrick (Frontiers in Public Health, 2017)
Background: The Convention on the Rights of Persons with Disabilities has received considerable attention internationally. Methods: The Convention’s main arguments are analyzed conceptually. Implications for the develop-ment of research designs are elaborated upon. Results: The Convention entails both a human-rights and a sociopolitical dimension. Advancing a rela-tional notion of disability, it enters a terrain rather foreign to the medical sciences. Research designs have to be changed accordingly. Conclusions: Research designs in accordance with the CRPD should employ and further develop context-sensitive research strategies and interdisciplinary collaboration. Complex designs that allow for a relational analysis of personalized effects need to be established and evaluated, thereby systematically integrating qualitative methods.